The Impact of Silver Nanoparticles Produced by Bacillus pumilus As Antimicrobial and Nematicide - Mahmoud, Wael M.; Abdelmoneim, Tamer S.; Elazzazy, Ahmed M. (Frontiers in Microbiology, 2016)
This study evaluates the potential application of silver nanoparticles (AgNPs) as antimicrobial or nematicidal agents produced by the extremophile Bacillus pumilus, which was isolated from the alkaline Wadi El-Natrun Lake in Egypt. The AgNPs were characterized by ultraviolet–visible absorption spectroscopy, transmission electron microscopy, and energy dispersive x-ray spectroscopy. The size of AgNPs formed ranged from 20.12 to 29.48 nm. Panagrellus redivivus was exposed to different concentrations (0, 50, 100, 150, and 200 µg/mL) of AgNPs in a 5 mL nematode suspension (1×103 mL-1). The best result occurred at AgNP concentrations of 150 and 200 µg/mL, with death rates of 80% and 91%, respectively, following 48 h of exposure. AgNPs also exhibited potent antimicrobial properties when using Gram-negative and Gram-positive human pathogens, with MIC and MBC values of 5 μg/mL and 10 μg/mL, respectively. These laboratory assays prove that biologically synthesized AgNPs are an ecofriendly material that can be used in lieu of solvents or toxic chemicals.